Ca-, Sr-, and Ba-Coordination polymers based on anthranilic acid via mechanochemistry. Issue 19 (17th April 2019) - Al-Terkawi, Abdal-Azim; Scholz, Gudrun; Prinz, Carsten; Emmerling, Franziska; Kemnitz, Erhard
Abstract : Ca-, Sr-, and Ba coordination polymers were obtained by milling metal-hydroxides with anthranilic acid. The metal cation radii influence the inorganic connectivity and dimensionality of structures. These compounds exhibit a phase transformation upon thermal annealing, which is a reversible process in Ba-CP. Abstract : Ca-, Sr-, and Ba-Based coordination polymers (CPs) were prepared mechanochemically by milling metal-hydroxide samples with anthranilic acid ( o ABAH). {[Ca( o ABA)2 (H2 O)3 ]} n (1 ) consists of one-dimensional polymeric chains that are further connected by a hydrogen-bonding network. {[Sr( o ABA)2 (H2 O)2 ]·H2 O} n (2 ) is a one-dimensional CP in which water molecules bridge Sr 2+ ions and increase the dimensionality by building an extended network. {[Ba( o ABA)2 (H2 O)]} n (3 ) crystallizes as a two-dimensional CP comprising one bridging water molecule. The cation radii influence the inorganic connectivity and dimensionality of the resulting crystal structures. The crystal structures were refined from powder X-ray diffraction data using the Rietveld method. The local coordination environments were studied via extended X-ray absorption fine structure (EXAFS) measurements. The compounds were further characterized using comprehensive analytical methods such as elemental analysis, thermal analysis, MAS NMR, imaging, and dynamic vapor sorption (DVS) measurements. Compounds1, 2, and3 exhibit small surface areas which decrease further after thermal annealing experiments. All compounds exhibit a phase transformation upon heating, which is only reversible in3 .